Uji efektivitas kombinasi pupuk bio-slurry dengan pupuk npk terhadap pertumbuhan dan produksi dua varietas padi sawah (oryza sativa L.) - Ahmad Khanafi; Yafizham Yafizham; Didik Wisnu Widjajanto (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
The objective of this research was to investigate the effectiveness of combination of bio-slurry fertilizer and NPK fertilizer on the growth and production of two varieties of rice. The experiment was assigned in a completely randomized design of factorial pattern. The first factor was the combination of bio-slurry and NPK fertilizer that consisted of P0 = no added fertilizer (control) 0 ton/ha, P1 = NPK fertilizer 550 kg/ha (165 kg N, 33 kg P, 45 kg K); P2 = bio-slurryfertilizer 2.3 tons/ha (45 kg N, 14 kg P, 23 kg K) and NPK fertilizer 400 kg/ha (120 kg N, 24 kg P, 32 kg K); P3 = bio-slurryfertilizer 4.6 tons/ha (90 kg N, 28 kg P, 46 kg K) and NPK fertilizer 250 kg/ha (75 kg N, 15 kg P, 20 kg K); P4 = bio-slurry fertilizer 5.9 tons/ha (115 kg N, 36 kg P, 59 kg K) and NPK fertilizer 100 kg/ha (30 kg N, 6 kg P, 8 kg K); and P5 = bio-slurryfertilizer 8.5 tons/ha (165 kg N, 52 kg P, 85 kg K). The second factor was varieties of rice that consisted of V1 : IR-64 and V2 : Ciherang. Each treatment was repeated three times. Parameters observed were plant height, number of tillers, weight of 1.000 grains, and rice production. Data were analyzed using ANOVA and continued with Duncan’s Multiple Range Test (DMRT). The results showed that the combination of bio-slurry fertilizer and NPK fertilizer were significantlyaffect (p <0.05)all observation parameters, while varieties of wetland rice did not show significant effect on all observation parameters (p<0.05). The application of bio-slurry fertilizer in single treatment or in either combination with NPK fertilizer had the same result with the treatment of NPK fertilizer on the growth and yield of rice. Keywords: rice, fertilizer combination, bio-slurry fertilizer, NPK fertilizer